Pembuatan Jobsheet Kendali Motor Induksi menggunakan Human Machine Interface - Riadotul Jannah; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
One of the practicum courses for the D3 Electrical Engineering study program in the Electrical Engineering Department is Electrical machine control practicum, some of the learning materials are about induction motor control with PLC which in the learning process uses trainers that are already based on PLC and equipped with HMI as teaching aids, but the availability of trainers is not yet equipped with a jobsheet as a guide in the learning process. Induction motor control practicum worksheet with PLC and HMI which is valid, practical and effective. Jobsheet making is done by research method 4D development, namely define, design, develop, and desiminate, and the validity test, practicality test, and effectiveness test have been carried out on the worksheet. The results of the validity test of the induction motor control practicum jobsheet with PLC and HMI are stated in the very valid category, the results of the practicality test of the jobsheet are stated in the very practical category and effectiveness test results josbheet declared effective.